2003
DOI: 10.1001/jama.289.18.2363
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Prevalence and Blood Pressure Levels in 6 European Countries, Canada, and the United States

Abstract: ARDIOVASCULAR DISEASE (CVD) remains the most common cause of death in industrialized countries, and hypertension is themostfrequenttreatableriskfactor.The analysis of international variation in risk factors has historically resulted in important insights into the etiology of CVD. 1 Moreover,internationalcomparisonsprovide useful information about achievable levels of risk reduction. Most etiologic research studies 1,2 on geographic variation in hypertension have investigated specific hypotheses, such as the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
635
8
69

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,520 publications
(800 citation statements)
references
References 31 publications
72
635
8
69
Order By: Relevance
“…Thus, for example, the prevalence of arterial hypertension could in the same study be found in about 28% of the North American populations and in 44% of the European population, and in addition with a great variation within Europe (ranging from the lowest frequency of 38% in Italy to the highest frequency of 55% in Germany) (Wolf‐Maier et al., 2003). Population‐based studies are therefore required in order to assess the prevalence of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for example, the prevalence of arterial hypertension could in the same study be found in about 28% of the North American populations and in 44% of the European population, and in addition with a great variation within Europe (ranging from the lowest frequency of 38% in Italy to the highest frequency of 55% in Germany) (Wolf‐Maier et al., 2003). Population‐based studies are therefore required in order to assess the prevalence of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients with unequivocal HCM may present with or develop some degree of hypertension, given the high prevalence of hypertension in the adult population 56. In most patients with hypertension, LV wall thickness is normal or only mildly increased (≤13 mm).…”
Section: Acquired Comorbiditiesmentioning
confidence: 99%
“…Given the increased myocardial mass and high myocardial oxygen demand, patients with HCM are particularly susceptible to the additional ischemic burden of one or multiple epicardial coronary artery stenosis 73. Not unexpectedly, CAD is a major prognostic indicator in HCM and is associated with an increase in overall mortality, SCD, and cardiac events, with a synergistic rather than additive effect 56. Preventive strategies for atherosclerotic disease should always be considered in patients with HCM and the standards for control of modifiable cardiovascular risk factors should arguably reflect those used for secondary rather than primary prevention of CAD because of the intrinsic frailty of the HCM myocardium to ischemic insults.…”
Section: Acquired Comorbiditiesmentioning
confidence: 99%
“…АГ является основной причиной смерти в мире [5] и встречается со стандартизованной по воз-расту и полу частотой от 28% в Северной Америке до 44% в европейских странах [6]. Примерно 54% всех случаев инсульта и 47% случаев ишемической бо-лезни сердца (ИБС) во всем мире связаны с повы-шенным артериальным давлением (АД) по результатам недавно опубликованного эпидемиоло-гического анализа [7].…”
Section: Possibilities To Achieve Target Bp Level According To the Leunclassified